„Na pograniczu... Najstarsze dzieje ziemi jarosławskiej” – nowa wystawa stała w Muzeum w Jarosławiu Kamienica Orsettich - Burghardt, Marcin; Sieradzka, Elżbieta (Muzeum Okręgowe w Rzeszowie, 2024)
Since June 21, 2024, the Museum in Jarosław the Orsetti House has presented a new permanent exhibition entitled “On the borderland... Jarosław Region in prehistory and the Middle Ages”. The exhibition shows, in an accessible manner, the communities that inhabited the area of today’s Jarosław district and surrounding regions, from the Late Palaeolithic (approx. 20–15 thousand years ago) to the Late Middle Ages (end of the 15th century). In this way, the Jarosław institution has become another museum in south-eastern Poland offering a permanent archaeological exhibition. The current exhibition is the third permanent exhibition of this kind in the history of the Jarosław institution. It is worth mentioning that the previous permanent archaeological exhibition in Jarosław was open many as 50 years ago. The decision to return to presenting archaeological topics in the museum’s permanent exhibitions was influenced by many factors – the main among them being the enormous increase in knowledge about the communities inhabiting south-eastern Poland in prehistoric and early historical periods, which has been observed since the early 20th century. Archaeological research performed in the region for over the last 20 years has led to many spectacular discoveries – noteworthy among them are the works carried out since 2016 in Chotyniec, the only Scythian culture hillfort in the area of Poland, located in the eastern part of Jarosław district. Work on the exhibition lasted almost two years. The implementation of the exhibition was co-financed by the Ministry of Culture and National Heritage under the program “Supporting Museum Activities.” The total cost of the project amounted to over 250,000 PLN. The title of the exhibition – “On the Borderland...” refers to the specific location of the present-day Jarosław district. This area, situated within the natural transport routes: the Przemyśl Gate and the San river valley, was at many times in history a place where cultural influences intersected along both the east-west and north-south axes. Due to the limited space available at the museum – the 16th-century Orsetti House – a single room, sized 11.5×3.3 meters, was allocated for the exhibition. It was assumed that each of the discussed time segments would be represented by one display case accompanied by a visual representation – a depiction of a person who lived during that particular historical period. Over 80% of the artefacts presented at the exhibition are the items from the own collection of the Museum in Jarosław the Orsetti House. This collection has been supplemented by copies, reconstructions, and replicas made especially for the exhibition, as well as materials from archaeological sites in the Jarosław region, borrowed from the National Museum of the Przemyśl Land in Przemyśl, the Regional Museum in Rzeszów, and the Institute of Archaeology at University of Rzeszów, in collaboration with the Foundation for Archaeological Centre in Rzeszów. One of the most distinctive elements of the exhibition is a mannequin displaying a reconstructed outfit and equipment of a warrior from the Scythian cultural circle. The exhibition is accompanied by a comprehensible catalogue, designed as a compact guide to the prehistory and Middle Ages of the Jarosław region. An important part of the project is also an educational program aimed primarily at students from the Jarosław district. The creation of the new archaeological exhibition “On the borderland... Jarosław Region in prehistory and the Middle Ages” is part of the expansion of the permanent exhibition of the Museum in Jarosław the Orsetti House related to the upcoming celebration of the 100th anniversary of the institution, which will take place in 2025. The exhibition, dedicated to the earliest history of the Jarosław land and located in the first exhibition hall, serves as an introduction to the rest of the museum’s displays.
“On the borderland... Jarosław Region in prehistory and the Middle Ages” – a new permanent exhibition at the Orsetti House Museum in Jarosław
Keywords: exhibition; museum; popularization of archaeology; Museum in Jarosław